PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUASAN ANGGOTA KOPERASI SIMPAN PINJAM KARYA MURNI MEDAN - Saragih, Nawary (Jurnal Manajemen dan Bisnis, 2019)
The purpose of this study was to determine the effect of the marketing mix of services on the satisfaction of members of the Cooperative Savings and Loans Work Purely Medan ". The type of research used is descriptive and quantitative. The research sample of 96 respondents with the method of sampling the maximum sampling error of the population is done randomly. The data needed is collected through a questionnaire. Data analysis method used is multiple linear regression analysis. The results obtained by the coefficient of determination (R2) of 0.979 means that the service marketing mix is able to explain the satisfaction of members in the Cooperative Savings and Loans Cooperative Medan of 97.9% and 2.1% again influenced by other factors not explained in this study. Regression equation Y = 1,464 + 0,696XÂ¬1 + 1,179X2 + 0,562X3 + 0,471X4-0,366X5 + 0,150X6 + 0,389X7-0,401X8 + Îµ. F test, where the significant level of 0.000 is smaller than the significant standard of 5% or 0.05, where the F-count is 511,235> F-table is 1.96, it can be concluded that the marketing mix of services has a positive and significant effect on Satisfaction of members of the Savings and Credit Cooperative Karya Murni Medan. T test, stated that product variables, price, place, promotion, and service operations have a positive and significant effect on member satisfaction. Physical evidence variable has positive effect, but it is not significant. The variable person / employee and customer service has a negative effect, but it is significant on member satisfaction. Suggestions, product variables, prices, places, promotions, and service operations have a positive and significant effect on member satisfaction needs to be maintained for member satisfaction. Variable people / employees, and customer service when viewed from the equation of negative regressions, then to overcome them needed improvements to the members' skills, neatness and politeness as well as attractive appearance of employees. Variable physical evidence to be more significant to overcome it requires improvements in the speed of service, speed of information provision, transparency in organizing the Annual Member Meeting and transparency in the election process of the board to achieve member satisfaction. Reviewing the entire system of service marketing mix variables that are member complaints in terms of loan interest rates offered, the length of time between an application and loan disbursement, the mismatch of the loan amount and approved, the amount of administrative costs and the burden of fines on loans.